Creation of aromatic maize by CRISPR/Cas. Issue 9 (21st June 2021) - Wang, Yanxiao; Liu, Xiaoqin; Zheng, Xiuxiu; Wang, Wenxia; Yin, Xunqing; Liu, Haifeng; Ma, Changle; Niu, Xiaomu; Zhu, Jian‐Kang; Wang, Fei
Abstract: Aroma is an important quality parameter for breeding in rice ( Oryza sativa ). For example, the aromatic rice varieties basmati and jasmine rice, with a popcorn‐like scent, are popular worldwide and routinely command a price premium. 2‐acetyl‐1‐pyrroline (2AP) is a key flavor compound among over 200 volatiles identified in fragrant rice. A naturally fragrant germplasm exists in multiple plant species besides rice, which all exhibit lower activity of BETAINE ALDEHYDE DEHYDROGENASE 2 (BADH2). However, no equivalent aromatic germplasm has been described in maize ( Zea mays ). Here, we characterized the two maize BADH2 homologs, ZmBADH2a and ZmBADH2b . We generated zmbadh2a and zmbadh2b single mutants and the zmbadh2a‐zmbadh2b double mutant by CRISPR/Cas in four inbred lines. A popcorn‐like scent was only noticeable in seeds from the double mutant, but not from either single mutant or in wild type. In agreement, we only detected 2AP in fresh kernels and dried mature seeds from the double mutant, which accumulated between 0.028 and 0.723 mg/kg 2AP. These results suggest that ZmBADH2a and ZmBADH2b redundantly participate in 2AP biosynthesis in maize, and represent the creation of the world's first aromatic maize by simultaneous genome editing of the two BADH2 genes. Abstract : Dysfunction of BETAINE ALDEHYDE DEHYDROGENASE 2 (BADH2) results in the accumulation of 2‐acetyl‐1‐pyrroline, a key fragrant compound of aromatic rice. Mutation of the two maize paralogs of BADH2 by CRISPR/Cas resulted in the creation of aromatic maize.